Lipopolysaccharide Stimulated the Migration of NIH3T3 Cells Through a Positive Feedback Between β-Catenin and COX-2 - Li, Xiao-Jun; Huang, Feng-Zhen; Wan, Yan; Li, Yu-Sang; Zhang, Wei Kevin; Xi, Yang; Tian, Gui-Hua; Tang, He-Bin (Frontiers in Pharmacology, 2018)
How β-catenin/COX-2 contribute to inflammation-induced fibroblasts migration remains poorly understood. Therefore, in this study, lipopolysaccharide (LPS) was used as a stimulus to accelerate the migration of NIH3T3 cells, which mimicked the tissue repair process. LPS treatment increased the cell migration in concentration-and time-dependent manner. And NS398, a COX-2 inhibitor, inhibited LPS-induced NIH3T3 cells migration. DKK-1, an antagonist of the Wnt/β-catenin signaling, also inhibited that migration. However, TWS119, an inducer of β-catenin via GSK-3β, increased the cell migration. LPS or TWS119 treatment increased COX-2, β-catenin, TGF-β1, and HMGB-1 expressions, and that could be attenuated by NS398 or DKK-1 addition. LPS induced the PGE2 production, and PGE2 increased the expression and nuclear translocation of β-catenin, while EP2 blocker, AH6809, alleviated those effects. TWS119 increased the luciferase activity in the COX-2 promoter. In conclusion, LPS stimulated the NIH3T3 fibroblasts migration through a positive feedback between β-catenin and COX-2, in which PGE2, EP2, TGF-β1, and HMGB-1 played as signal molecules.